Economic transition in Central and Eastern Europe planting the seeds - Gros, Daniel 1955- (Cambridge University Press, 2004)
Analysing the key problems facing the transition countries in Central and Eastern Europe, this accessible book describes the legacy of the central planners, the progress achieved so far and the need for further reforms. It documents the outstanding successes and failures, and analyses why certain approaches to transition have worked and others have not. It tests where transition is over and shows how some countries have graduated from 'transition' to 'integration' through their efforts to join the European Union (EU). It discusses the costs and benefits of the eastern enlargement of the EU. The specific experiences of German unification, the Soviet Union's disintegration, and Russia's complex reforms are examined, as are the specific issues that need to be addressed in the Balkans. The book concludes by indicating how the expanding EU could help the poor performers through inclusion in a continent-wide integrated economic area
Title from publisher's bibliographic system (viewed on 05 Oct 2015)
Keywords: Europäische Union; Geschichte 1989-2000; Geschichte 1990-2000; Wirtschaftspolitik; Free enterprise / Europe, Eastern; Free enterprise / Europe, Central; Post-communism / Europe, Eastern; Post-communism / Europe, Central; Wirtschaftsentwicklung; Beitrittsstaaten; Wirtschaftsreform; Erweiterung; Europe, Eastern / Economic policy / 1989-; Europe, Central / Economic policy; Osteuropa; Transformationsländer